(untitled) (Journal of the Management Sciences, 2026)
The study examined the effect of Audit Report Quality on Corporate Governance and Accounting Information Systems of SMEs in Lagos State, Nigeria . The objectives of the study were to examine the effect of audit report quality on corporate governance of SMEs and to assess the effect of audit report quality on the accounting information systems of SMEs in Lagos State. Survey research design was employed. The population of the study were 8,395 registered SMEs in Lagos. The Krejcie and Morgan statistical table (1970) for sample size determination was adopted to determine the sample size. Simple random sampling technique was used to choose the right participants. Data for the study was analyzed with percentage, and frequency distribution. Hypotheses were tested using linear regression analysis with SPSS version 25.0. The study found that audit report quality has a positive significant effect on corporate governance of SMEs in Lagos State (R=.613a, R2 =.376, F-stat=209.275, p =.000). The study in addition, discovered that audit report quality has a significant and positive effect on accounting information system of surveyed SMEs in Lagos State (R=.496a, R2 =.246, F-stat=113.730, p =.000). The study recommended that SMEs should always prepare and submit their audited account on time, so as to maintain good reputation and avoid penalty by government authorities. In addition, corporate governance of SMEs should imbibe the culture of timely preparation of financial statements for effectiveness and efficiency